2011
DOI: 10.1080/00450618.2011.563246
|View full text |Cite
|
Sign up to set email alerts
|

The influence of front-loading and top-loading washing machines on the persistence, redistribution and secondary transfer of textile fibres during laundering

Abstract: This study investigated the influence of several factors on the redistribution of extraneous textile fibres on garments during machine washing. Cotton T-shirts were seeded with known numbers of acrylic, wool and viscose target fibres in controlled positions and laundered in top-and front-loading machines, both individually and accompanied by undergarments. The persistence of target fibres was low (generally 510%), but never zero. Between 50% and 100% of recovered fibres were redistributed away from the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Intermediate variability in decay may be attributed to various factors: the reincorporation of diatoms within a clothing garment during activity, or the introduction of additional diatoms from postcrime scene environments during each experimental run. Previous research has shown that forensic indicators including pollen, UV powder, and fibres can be redistributed within a clothing garment during wear, and when machine washed or packaged as an evidential exhibit [31][32][33][34]. For example, one study demonstrated that despite shedding from the initial transfer area, pollen grains were not lost from the entire system but rather redistributed within a clothing item [31].…”
Section: Variable Intermediate Decay (4-48 H)mentioning
confidence: 99%
“…Intermediate variability in decay may be attributed to various factors: the reincorporation of diatoms within a clothing garment during activity, or the introduction of additional diatoms from postcrime scene environments during each experimental run. Previous research has shown that forensic indicators including pollen, UV powder, and fibres can be redistributed within a clothing garment during wear, and when machine washed or packaged as an evidential exhibit [31][32][33][34]. For example, one study demonstrated that despite shedding from the initial transfer area, pollen grains were not lost from the entire system but rather redistributed within a clothing item [31].…”
Section: Variable Intermediate Decay (4-48 H)mentioning
confidence: 99%